Effect of Staphylococcus aureus Thermostable DNase on Some Immunological Parameters - Noor Naeem Khwen; Sawsan Hassan Authman; Mohammed Faraj AL- Marjani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Thermostable DNase was purified from Staphylococcus aureus isolated from local clinical source. Thecurrent study includes different immunological assays to evaluate the role of purified DNase. The phagocyticactivity showed that the group of mice infected with P.aeruginosa recorded the highest values with significantdifferences (P <0.05) in comparison with the group that received mixed injection of 1 µg /ml of DNase and P.aeruginosa showed decrease in phagocytic activity followed by group that injected by 1 µg /ml DNase onlywith phagocytic activity 2%. DNase has a positive immunomodulatory effect on IL-10 and IL-4 level. Thedata showed that the highest value of IL-10 is in group that injected with 1 µg /ml DNase only (IV group)was 86.79±1.68. While the highest value of IL-4 was in group that injected with both DNase (1 µg /mouse)and P.aeruginosa gave the highest values (III group) was 84.02 ±1.19. In Arthus reactions(Immediate typehypersensitivity), the group that have been injected with both DNase and P. aeruginosa (group III ) gave thehighest values (4.50±0.70) while in delayed type hypersensitivity the same group III showed higher valuesafter 24 and 48 hrs (5.00±0.00) , (4.00±0.00) respectively.